Entrepreneurial Education in A Cash-Strapped Economy: the Case of the Nigerian Army Tertiary Institutions - Ubabudu Mary Chinelo; Basharu Ismail Aminu (International Journal on Economics, Finance and Sustainable Development, 2022)
The dwindling Nigerian economy has increased the funding constraints for educational institutions. This study, therefore, examines the current measures used by five Nigerian Army higher institutions (NATIs) to implement entrepreneurial education and the financial-related challenges facing them. The research design adopted for this work is the survey method. Census technique was used in the study with questionnaire administered to fifty-three respondents from the five schools. The Cronbach’s Alpha (α) test conducted produced a reliability coefficient of 0.843. The result shows that 66% of the respondents opined that resources are not being effectively deployed for entrepreneurial education. More than a fifth (22.6%) of the staff employed to teach entrepreneurial education in schools lack competences and skills that are necessary for the actualization of the goals of entrepreneurial education. About three-quarter (75.5%) of the respondents posits that inadequate funds affects provision of facilities for teaching of entrepreneurial education. Similar high proportion of respondents believe insufficient funds have impeded collaboration with entrepreneurs as resource persons and provision of in-service training of manpower in new innovations; while a smaller proportion (43.2%) of respondents opined that there is greater use of theory rather than practical in classrooms. To effectively implement entrepreneurial education in NATIs, the school managements should utilize the available resources correctly, incorporate the use of more home-grown technology which are relatively less expensive, encourage robust collaboration with entrepreneurs who are willing to act render services more as community service and seek increase access to Tertiary Education Trust Fund (Tetfund).